PENGARUH VIDEO TUTORIAL MEDIA SOSIAL TERHADAP KETERAMPILAN MENJAHIT BUSANA WANITA SISWA SMK DESAIN PRODUKSI BUSANA - Haniatul Masruroh; Ana Sri Gundari; Desi Tri Rahayuningsih (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Sewing skills for women's clothing are a core competency that must be mastered by students in the Fashion Design and Production Vocational Program (DPB) of Indonesian vocational high schools (SMK). Preliminary observations found that a large proportion of Grade X DPB students still had difficulty mastering basic sewing techniques, while the relationship between the use of social media-based video tutorials as an independent learning source and students' actual sewing skills has rarely been examined empirically with rigorous statistical testing. This study aimed to determine (1) the relationship, (2) the effect, and (3) the magnitude of the effect of social media-based video tutorials on women's clothing sewing skills. A quantitative correlational design with simple linear regression was employed. The population and sample consisted of all 35 Grade X DPB students of one vocational high school (total sampling/sampling jenuh). Variable X (use of social media video tutorials) was measured with a 20-item Likert questionnaire covering four indicators (content quality, platform accessibility, usage intensity, direct application), while Variable Y (sewing skills) was measured with a 20-item self-report Likert questionnaire covering four indicators (basic technique understanding, pattern-making, sewing process, final result). Both instruments showed excellent internal consistency (Cronbach's alpha = .957 across all 40 items). Data were analyzed using the Kolmogorov-Smirnov (Lilliefors) normality test on the regression residuals, Pearson product-moment correlation, and simple linear regression. Descriptive scores (theoretical range 20-100) showed a mean of 77.6 (SD = 8.8) for Variable X and 75.1 (SD = 11.9) for Variable Y. The regression residuals showed an indication of non-normality (Kolmogorov-Smirnov p = .012), so the t-test and regression results are interpreted as preliminary evidence pending confirmation with non-parametric tests or a larger sample. A significant positive correlation was found (Pearson r = .668, p < .001), and simple linear regression yielded Y = 5.411 + 0.899X (t = 5.153 > t table 2.035; R2 = .446), indicating that the use of social media video tutorials contributed 44.6% to the variance in sewing skills. It is concluded that social media-based video tutorials have a significant positive effect on women's clothing sewing skills among DPB students and can be recommended as a structured supplementary learning medium.